Measuring Higgs coupling to tau-leptons at future e(+)e(-) colliders - Chalov, A.; Likhoded, A.; Rosenfeld, Rogério [UNESP] (Iop Publishing Ltd, 2003)
We perform a complete simulation of the process e(+)e(-) --> tau(+)tau(-)nu(ν) over bar where nu can be an electron, muon or tau neutrino, in the context of a general Higgs coupling to tau-leptons. We analyse various kinematical distributions and obtain the sensitivity regions in the parameter space that can be explored at a future e(+)e(-) collider. In particular, inclusion of W boson fusion enhances the sensitivity significantly.